Extended high resolution analysis of the second triad of D232S, D233S and D234S. (April 2020) - Ulenikov, O.N.; Bekhtereva, E.S.; Gromova, O.V.; Belova, A.S.; Sydow, C.; Maul, C.; Bauerecker, S.
Highlights: FTIR spectra of the second triad of D 2 32 S, D 2 34 S, and D 2 33 S are recorded. Ground state parameters and pure rotational energies of D233S are determined. Band centers, rotational, centrifugal distortion and resonance interaction parameters of the second triad are determined for all three isotopologues. Abstract: The high resolution infrared spectra of deuterated hydrogen sulfide D 2 32 S were recorded with a Bruker IFS 125HR Fourier transform infrared spectrometer and analyzed in the region of 2400–2900 cm − 1 where three ν 1 + ν 2, ν 2 + ν 3 and 3 ν 2 interacting bands are located. 4227 transitions with maximum values of the quantum numbers J max = 28/28/20 and K a max = 18/19/11 were assigned in the experimental spectra to the ν 1 + ν 2, ν 2 + ν 3 and 3 ν 2 bands. On this basis, 399/439/216 upper ro–vibrational energies were obtained for the upper vibrational states (110), (011) and (030) (about 43% more for the number of ro–vibrational energy values and about 63% more for the number of assigned transitions compared to preceding studies). These data were used in the weighted fit of the Watson Hamiltonian parameters. The 97 parameters obtained from the fit reproduce the 1054 initial energy values of three vibrational states used in the fit with the root mean square deviation d rms = 1.97 × 10 − 4 cm − 1 . The 1215 and 56 transitions belonging to the ν 1 + ν 2 and ν 2 + ν 3 bands of the D 2 34 S and D 2 33 S species (410 and 30 upper energy values, respectively) were recorded and analysed for the first time. The ground vibrational state parameters of D 2 33 S are determined from experimental combination differences.